Information and Communications Technology and Inventory Management amongst Breweries in Nigeria - Grace O. Akinola; Olusegun Timothy Odesola (Universitas Airlangga, 2018)
This study examined the effect of ICT on inventory management amongst breweries in Nigeria. Secondary data were sourced for this study. The population for the study comprises all brewery companies quoted on the Nigerian Stock Exchange. Purposive sampling technique was used in selecting the three leading brewery companies in Nigeria, namely the Nigerian Breweries Plc; Guinness Nigeria Plc; and International Breweries Plc that represent 75% of the breweries quoted in the Nigerian Stock Exchange factsbook. Secondary data on ICT/ software costs, inventories, sales turnover/revenue, and assets were sourced from years 2006 to 2015 Annual Reports and Statements of Accounts of the three selected breweries and the Nigeria Stock Exchange facts book. The data collected were analyzed using descriptive statistics ( tables, mean and standard deviation) and inferential statistics (Ordinary Least Square (OLS) method). The results also showed that ICT usage had no significant positive relationship on inventory management (t = 0.021, P > 0.01). The study concluded that ICT had no significant positive effect on inventory management in the Nigerian Brewery industry. It is recommended that brewery firms in Nigeria should deploy the right software for inventory management. The limitation of this research is what were used to measure the inventory management and Information and Communications Technology (ICT) as contrary results could be obtained if these variables are measured using other yardsticks. The improvement of the respondent required to see the other problem and another kind of business.